2008
DOI: 10.1093/bioinformatics/btn550
|View full text |Cite
|
Sign up to set email alerts
|

SPOCTOPUS: a combined predictor of signal peptides and membrane protein topology

Abstract: SPOCTOPUS is available as a web server and both the source code and benchmark data are available for download at http://octopus.cbr.su.se/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
180
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(182 citation statements)
references
References 10 publications
0
180
0
Order By: Relevance
“…In essence, a great concentration of turn-promoting residues is found in the region connecting HR1 and HR2. Thus, in the membrane-bound form, we can expect the turn of viroporin 2B to be centered on 56 RNYED 60 . Interestingly, previous mutagenesis studies using the CBV 2B protein showed that the negatively charged residues found in this short hydrophilic turn between HR1 and HR2 are indeed important for the membrane-active character of 2B protein (16).…”
Section: Discussionmentioning
confidence: 99%
“…In essence, a great concentration of turn-promoting residues is found in the region connecting HR1 and HR2. Thus, in the membrane-bound form, we can expect the turn of viroporin 2B to be centered on 56 RNYED 60 . Interestingly, previous mutagenesis studies using the CBV 2B protein showed that the negatively charged residues found in this short hydrophilic turn between HR1 and HR2 are indeed important for the membrane-active character of 2B protein (16).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary structure predictions were made by SAM and PSI-PRED (19,22). Transmembrane helix topology predictions were made using TMHMM, Memsat, and Spoctopus (22,31,39). Tertiary predictions were performed using RosettaMembrane (2).…”
Section: Construction Of Csfv Mutantsmentioning
confidence: 99%
“…Machine learning-based predictors, trained and validated using topology data derived from structural data combined with evolutionary information, now achieve prediction accuracies in the range 80-90% (2,3). Another approach, based on an experimental scale of position-specific amino acid contributions to membrane insertion free energy, achieves similar accuracy suggesting that predicting TMP topology from first principles is an achievable goal (4).…”
mentioning
confidence: 96%